2023
DOI: 10.1111/jopy.12803
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and distal honor fit and subjective well‐being in the Mediterranean region

Abstract: The data and syntax that support the findings of this study and produced this manuscript are openly available in the Open Science Framework at https://osf.io/4tyk5/. The current research and analyses were not pre-registered at an independent repository.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Future research should manipulate the salience or centrality of relevant identities to further investigate its causal impact on the endorsement of honor values, together with honor’s implications for social behavior, attitudes, and other psychological characteristics. For instance, research has shown that individuals’ endorsement of honor is linked to increased well-being when it aligns with the honor endorsement by others in one’s (distal or proximal) social environments ( Kirchner-Häusler et al, 2024 ). Findings from this study suggest that, because honor may constitute the content of relevant social identities, it may unlock the potential of identities to enhance well-being by providing individuals with guidance on the norms and behaviors suitable for their respective contexts ( Haslam et al, 2018 ; Travaglino et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research should manipulate the salience or centrality of relevant identities to further investigate its causal impact on the endorsement of honor values, together with honor’s implications for social behavior, attitudes, and other psychological characteristics. For instance, research has shown that individuals’ endorsement of honor is linked to increased well-being when it aligns with the honor endorsement by others in one’s (distal or proximal) social environments ( Kirchner-Häusler et al, 2024 ). Findings from this study suggest that, because honor may constitute the content of relevant social identities, it may unlock the potential of identities to enhance well-being by providing individuals with guidance on the norms and behaviors suitable for their respective contexts ( Haslam et al, 2018 ; Travaglino et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kirchner‐Häusler et al (2023, this issue) examined how the fit in honor values among participants from a multinational sample living in the Mediterranean region is linked to participants' well‐being. The authors tested whether a distal honor fit (i.e., own honor values and perceived societal honor values) or a proximal honor fit (i.e., own honor values and group‐level honor values) are linked to well‐being.…”
Section: Overview Of Papersmentioning
confidence: 99%
“…This special issue highlights that the call to go beyond traits is still relevant. However, we want to point to the few articles in our special issue that went beyond traits (e.g., Atherton et al, 2023; Du et al, 2023; Kandler et al, 2023; Kirchner‐Häusler et al, 2023). These included personality constructs such as values, well‐being, goals, interests, religiousness, and self‐schemas.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation